Leptospirosis presenting with acute renal failure, thrombocytopenia, and hyperbilirubinemia - Esravila Ariya Wibisono; Yuscha Anindya (Jurnal Kedokteran Syiah Kuala, 2022)
Leptospirosis is a spirochaetal zoonotic disease associated with a broad spectrum of clinical manifestations from asymptomatic to multi-organ failure and death. Acute liver and renal involvement in severe forms of leptospirosis is known as Weil’s disease. Gold-standard serology test results may delay treatment and can cause rapid clinical deterioration. We present a patient with severe leptospirosis that was treated with empiric treatment without confirming the gold-standard confirmatory serology tests.